Financial health and customer satisfaction in private health care providers in Brazil Desempenho financeiro e satisfação do consumidor das operadoras de saúde suplementar no Brasil - Rafael Felipe Schiozer; Cristiana Checchia Saito; Richard Saito (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2011)
This paper analyzes the relationship between the financial health and organizational form of private health care providers in Brazil. It also examines the major determinants of customer satisfaction associated with the provider's organ-izational form. An adjusted Altman's z-score is used as an indicator of financial health. A proxy variable based on customer complaints filed at the Brazilian National Agency for Supplementary Health is used as an indicator for customer satisfaction. The study uses a sample of 270 private health care providers and their operations over the period 2003-2005. Panel data analysis includes control variables related to market, operations, and management. Principal results indicate that: (1) private health care providers benefit from economies of scale; (2) self-funded health plans have better financial health; (3) spending on marketing does not have a signif-icant impact on customer satisfaction in Brazil; (4) weak empirical evidence exists showing that good financial performance enhances customer's satisfaction. Este artigo analisa a situação financeira das operadoras de saúde suplementar no Brasil, de acordo com a modalidade de gestão. Adicionalmente, examina os principais determinantes para a satisfação do consumidor desses serviços. Como indicador principal de saúde financeira, utiliza-se uma versão adaptada do z-score de Altman. A proxy para satisfação do consumidor é o nível de reclamações fundamentadas registradas junto à Agência Nacional de Saúde Suplementar. Utilizamos uma amostra de 270 operadoras de saúde suplementar para o período 2003-2005, e regressões de dados em painel, com variáveis de controle de mercado, operacionais e de gestão. Os resultados principais indicam que (1) as operadoras de saúde se beneficiam de economias de escala; (2) as empresas que operam no modelo de autogestão têm situação financeira melhor que as demais; (3) as despesas com marketing não impactam a satisfação dos consumidores dos planos de saúde; (4) finalmente, encontra-se também alguma evidência empírica indicando que a boa situação financeira implica maior satisfação do consumidor.